Ambient air pollution exposure and depressive symptoms: Findings from the French CONSTANCES cohort. (December 2022) - Zare Sakhvidi, Mohammad Javad; Lafontaine, Antoine; Lequy, Emeline; Berr, Claudine; de Hoogh, Kees; Vienneau, Danielle; Goldberg, Marcel; Zins, Marie; Lemogne, Cédric; Jacquemin, Bénédicte
Abstract: Background and Aim: Few studies have reported the association between air pollution exposure with different dimensions of depression. We aimed to explore this association across different dimensions of depressive symptoms in a large population. Methods: Data from the enrollment phase of the French CONSTANCES cohort (2012–2020) were analyzed cross-sectionally. Annual concentrations of particulate matter with a diameter < 2.5 µm (PM2.5 ), black carbon (BC), and nitrogen dioxide (NO2 ) from the land-use regression models were assigned to the residential addresses of participants. Total depressive symptoms and its four dimensions (depressed affect, disturbed interpersonal relations, low positive affect, somatic complaints) were measured using Centre of Epidemiologic Studies Depression questionnaire (CES-D). We reported results of negative binomial regression models (reported as Incidence Rate Ratio (IRR) and 95 % confidence interval (CI) for an interquartile range (IQR) increase in exposure), for each pollutant separately. Stratified analyses were performed by sex, income, family status, education, and neighborhood deprivation. Results: The study included 123, 754 participants (mean age, 46.50 ± 13.61 years; 52.4 % women). The mean concentration of PM2.5, BC and NO2 were 17.14 µg/m 3 (IQR = 4.89), 1.82 10 -5 /m (IQR = 0.88) and 26.58 µg/m 3 (IQR = 17.41) respectively. Exposures to PM2.5, BC and NO2 were significantly associated with a higher CES-D total (IRR = 1.022; 95 % CI = 1.002: 1.042, IRR = 1.027; 95 % CI = 1.013: 1.040, and IRR = 1.029; 95 % CI = 1.015: 1.042 respectively), and with depressed affect, and somatic complaints. For all pollutants, a higher estimate was observed for depressed affect. We found stronger adverse associations for men, lower-income participants, low and middle education groups, those living in highly deprived areas, and single participants. Conclusion: Our finding could assist the exploration of the etiological pathway of air pollution on depression and also considering primary prevention strategies in the areas with air pollution.